Bringing Aztlan to Mexican Chicago : My Life, My Work, My Art - González, Jose Gamaliel, 1933- (Book collections on Project MUSE., 2010)
Bringing Aztlán to Mexican Chicago is the autobiography of Jose Gamaliel González, an impassioned artist willing to risk all for the empowerment of his marginalized and oppressed community. Through recollections emerging in a series of interviews conducted over a period of six years by his friend Marc Zimmerman, González looks back on his life and his role in developing Mexican, Chicano, and Latino art as a fundamental dimension of the city he came to call home.;; Born near Monterrey, Mexico, and raised in a steel mill town in northwest Indiana, González studied art at the School of the Art Institute of Chicago and the University of Notre Dame. Settling in Chicago, he founded two major art groups: El Movimiento Artístico Chicano (MARCH) in the 1970s and Mi Raza Arts Consortium (MIRA) in the 1980s. ;; With numerous illustrations, this book portrays González's all-but-forgotten community advocacy, his commitments and conflicts, and his long struggle to bring quality arts programming to the city. By turns dramatic and humorous, his narrative also covers his bouts of illness, his relationships with other artists and arts promoters, and his place within city and barrio politics.